ANALYSIS OF THE IMPACT OF POPULATION GROWTH IN INDONESIA - Simangunsong, Yehezkiel Austincamry; Hutasoit, Imelda; Julian, Edwin; S, Miswar; Praing, Umbu Kanni (Registratie, 2024)
This literature review analyzed findings published in academic journals, focusing on the impact of population growth on various aspects of Indonesia's environment. The study employs a qualitative research approach using literature review methods to identify, analyze, and explore previous research results. The findings indicate that high population growth can lead to several issues, including decreased population welfare, heightened potential for conflict, increased competition for employment, housing, and natural resources, and a decline in environmental quality. The deterioration in environmental quality is evident in the decline of water, air, and land quality. To address the consequences of rapid population growth, it is essential to implement measures for population control and to enhance welfare through targeted programs